Análisis Jurídico y Doctrinario a la Figura Jurídica de Aposición o Fijación de Sellos respecto al derecho Sucesorio - Sotomayor Granda, Anahí Valentina (2023)
The present research work entitled " Análisis Jurídico y Doctrinario a la figura jurídica de Aposición o Fijación de Sellos respecto al Derecho Sucesorio ". It has the purpose of making a doctrinal analysis, regarding the security measure of fixation or apposition of seals with respect to inheritance law. It is also intended to develop a legal analysis on the non-typification of the affixation or affixation of seals as an insurance measure in civil matters regarding inheritance law, and through this to promote within our legal framework, policies, projects and laws framed in civil law and the procedures to be followed to facilitate the actions of judges, thereby contributing to legal development and ensuring an adequate and conducive administration of justice regarding inheritance law. The present legal research consists of the demonstration of the existing legal absence on the security measure of Apposition or Fixation of seals, with respect to the inheritance law, in such a way it is of transcendental importance since previously we had the Civil Procedure Code, where some of its articles contemplated a more detailed manner in which the judges could act before a measure filed by the heirs or persons having an interest in the custody and seals of personal property and documents arising from the death of a person, which subsequently will be included in the solemn inventory, through a voluntary procedure, as it is provided for in the General Organic Code of Processes. Likewise, to promote that access to justice is effective and safe, respecting the right to legal certainty enshrined in the Constitution of the Republic of Ecuador. The execution of this work is feasible since it has bibliographic sources, documents, methodological guidance, field studies and other resources that make its development feasible. For the above mentioned, it can be summarized that the present legal research work involves essential aspects that ensure the protection of the principles established in the Constitution of the Republic 5 of Ecuador, among them mainly the procedural speed, so that the heirs have a clear and effective means to make effective the diligence of custody and sealing of movable property, documentation, among others.